SECURE AND EFFICIENT DATA TRANSMISSION IN WIRELESS MEDICAL SENSOR NETWORKS - Prasanth, M.; Madhavi, S (IJRDO -Journal of Computer Science Engineering, 2015)
Wireless medical sensor networks (MSNs) have emerged as a promising technique which will revolutionize the way of seeking healthcare at home, hospital, or large medical facilities. E-healthcare collects patient’s vital body parameters by wearable or implantable biosensors. However, designing a secure and efficient system for MSNs is a difficult task. In this paper, we propose a lightweight and secure system for MSNs. we have identified the security challenges facing an MSN for wireless health monitoring and then proposed a novel and lightweight system to achieve secure data transmission and access control for MSNs. The security analysis has demonstrated that our system can achieve the requirements of the protocol of this kind. Our system only requires symmetric-key encryption/decryption and hash operations and is thus suitable for low-power sensor nodes. To the best of our knowledge, this is the first secure data transmission and access control system for MSNs until now